2001
DOI: 10.1002/jbm.1211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water vapor treatment on apatite formation on precalcified titanium and bond strength of coatings to substrates

Abstract: In previous investigations, a simple method, precalcification, was developed for bioactivating titanium. After a titanium sample was precalcified in a boiling saturated Ca(OH)(2) solution and then immersed in a calcium phosphate supersaturated solution, an apatite coating rapidly precipitated onto its surface. In the present study, heat-treatment in water vapor was carried out prior to precalcification. Heat-treatment in water vapor stimulated the chemical reaction between titanium, calcium, and phosphate. Coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…For example, if CaPO 4 needs to be biomimetically deposited on titanium or its alloys, a surface layer of titanium oxides, hydroxides and/or titanates should be created prior the deposition [323]. This can be done by various oxidation techniques, such as heat [324] or alkali [49,128,325,326] treatments, oxidation in H 2 O 2 [128,326], micro-arc oxidation [327], precalcification in boiling Ca(OH) 2 solution [328,329] or under the hydrothermal conditions [330], as well as by water vapor treatment [331]. Similar is valid for other chemically inert metals: prior biomimetic deposition of CaPO 4 , a surface layer of hydrated zirconium hydroxides, niobium hydroxides, tantalum hydroxides or their Na-or K-containing salts should be created on the surface of Zr, Nb and Ta, respectively [332,333].…”
Section: Wet Techniquesmentioning
confidence: 99%
“…For example, if CaPO 4 needs to be biomimetically deposited on titanium or its alloys, a surface layer of titanium oxides, hydroxides and/or titanates should be created prior the deposition [323]. This can be done by various oxidation techniques, such as heat [324] or alkali [49,128,325,326] treatments, oxidation in H 2 O 2 [128,326], micro-arc oxidation [327], precalcification in boiling Ca(OH) 2 solution [328,329] or under the hydrothermal conditions [330], as well as by water vapor treatment [331]. Similar is valid for other chemically inert metals: prior biomimetic deposition of CaPO 4 , a surface layer of hydrated zirconium hydroxides, niobium hydroxides, tantalum hydroxides or their Na-or K-containing salts should be created on the surface of Zr, Nb and Ta, respectively [332,333].…”
Section: Wet Techniquesmentioning
confidence: 99%
“…Our previous works [19,24] have revealed that the structure and composition of the Ca-P coating on Ti surface by electrodeposition method is not crystalline apatite, but mainly composed of plate-like OCP, amorphous apatite and some apatite. Some authors considered that the significant needle-like crystals are apatite observed with biomimetic coating immersed in 0.1 M NaOH solution [38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…2B. Deconvolution of the O 1s peak revealed three sub-peaks of oxygen for PTi surface: (1) in TiO 2 , (2) in absorbed water, (H 2 O) ab and in acidic hydroxyl, (OH) a , and (3) in chemically absorbed basic hydroxyl, (OH) b , groups [22][23][24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After precalcification, a uniform calcium phosphate rapidly precipitated onto the surfaces of titanium in SCS (Feng et al, 2002a). Later, heat-treatment in water vapor was carried out prior to precalcification to improve the bond strength of the apatite coating to substrate (Feng et al, 2002b). Precalcification was also applied to AA-or AH-treated titanium by soaking them in Na 2 HPO 4 and then saturated Ca(OH) 2 solution before immersion in SCS or SBF to speed up the formation of apatite (Liang et al, 2003;Wen et al, 1997).…”
Section: Precalcificationmentioning
confidence: 99%